Flexible OPV modules for highly efficient indoor applications - Ylikunnari, Mari; Välimäki, Marja; Väisänen, Kaisa-Leena; Kraft, Thomas M; Sliz, Rafal; Corso, Gianni; Po, Riccardo; Barbieri, Riccardo; Carbonera, Chiara; Gorni, Giacomo; Vilkman, Marja (Flexible and printed electronics, 2020)
The comparison of solution processed organic photovoltaics with two roll-to-roll coated electron transport layers (ETL), as well as printed grid or solid back electrodes provides insight into the future of R2R fabricated architectures. The variation in performance of the R2R slot-die coated zinc oxide (ZnO) versus the tin oxide (SnO2), showed a clear dependence on the spectrum of the illumination source. It was found that under indoor light conditions (200-1000 lux LED and fluorescent sources) the SnO2 outperformed the ZnO with highest efficiencies near 13% and 10% respectively. This is in contrast to results obtained under 1 Sun (AM 1.5) in which the cells fabricated with a ZnO ETL had a higher power conversion efficiency than those prepared with SnO2. The results also confirm the significance of the layout of the printed silver back contact; in which cells with the grid structure outperformed those with full coverage by approximately 35% for ZnO and just under 10% for SnO2 (all light conditions). The combination of a R2R coating and S2S printing process to prepare modules with 8 cells in series (PET/ITO/SnO2/PV2001:PCBM/PEDOT:PSS/silver grid) resulted in a PCE of 13.4% under indoor office light conditions.